Islamic reform and conservatism: Al-Azhar and the evolution of modern Sunni Islam - Gesink, Indira Falk (Library of modern religion, 2010)
The famed reform debates at al-Azhar Madrasa in nineteenth-century Cairo -- one of the most influential centers of religious study in Sunni Islam -- were enormously influential for twentieth-century Islamic thought. In this book Indira Gesink argues that narratives of these debates overemphasize the roles of famous modernists like Muhammad ʹAbduh, obscuring important themes. By restoring conservative voices to the debate, she shows that conservative ʹulama engaged many of the same issues as reformers and led committees that generated and implemented reforms; ultimately, conservative leaders at al-Azhar provided crucial legitimacy for the reforms to become rooted in public life. Drawing on obscure, but important, archival sources to illustrate the important contributions of conservative scholars to the evolutionof twentieth-century Sunni Islam, Islamic Reform and Conservatism is indispensable for all those interested in the modern Middle East, religious history, secularism, modernism and religious reform. -- Book jacket